(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A Microfinance Management System: Logistic 1 is essential for managing the items and equipment stored in RGBC’s inventory. The whole procedure of tracking and monitoring is simplified through an online system. The Microfinance Management System: Logistic 1 enables RGBC company to handle data and monitor reports efficiently. This system reduces time, eliminates the need for human record-keeping, and lowers mistake rates. The developers provide the system that satisfies the company’s needs, enhances the management of the company’s project, and improves the monitoring of the items and equipment in the company. Creating a Microfinance Management System: Logistic 1 brings several constraints and obstacles during implementation. The main challenges encountered during the development of the system were: There was an error in the code creation. Thus, the system needs to be fixed; this requires more focus on creating the system and also teamwork. Another challenge is integrating the microfinance management system: logistic one into other sub-systems of the microfinance system. The process may require significant resources and technical expertise to ensure that the System functions smoothly and effectively with other IT systems. Overall, Microfinance Management System: Logistic implementation can present several challenges, but with careful planning and coordination, these can be solved. Implementing this system improved the operations and functionality of the logistics department. The goals achieved after finishing the Microfinance Management System: Logistic 1 are efficient monitoring of the ongoing and finished project and correctly and efficiently monitoring or tracking the files, documents, and items that enter our system. The developers were confident that the system would have a better process and be used appropriately without error.